2018
DOI: 10.1016/j.actpsy.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Prolonging the response movement inhibits the feed-forward motor program in the sustained attention to response task

Abstract: Despite widespread use in clinical and experimental contexts, debate continues over whether or not the Sustained Attention to Response Task (SART) successfully measures sustained attention. Altering physical aspects of the response movement required to SART stimuli may help identify whether performance is a better measure of perceptual decoupling, or response strategies and motor inhibition. Participants completed a SART where they had to manually move a mouse cursor to respond to stimuli, and another SART whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…Considering the SART-C and SART-S conditions collectively, modulating the response characteristics by increasing the response from a single-button to a multiple-button response facilitated a 9% error of commission rate and response latency of 807 ms. Conversely, the traditional SART, which uses a single-button response, produces a relatively higher error-rate range (29%-55%) with a faster response latency range of 325-421 ms Helton, 2009;Helton, Head, & Russell, 2011;Helton, Kern, & Walker, 2009;Manly et al, 2003). As similarly found in point-and-click SARTs Wilson et al, 2018), changing the motor-response characteristics decreases response inhibition errors as measured by errors of commission; however, the cost of improved accuracy was slower response times to Go stimuli.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Considering the SART-C and SART-S conditions collectively, modulating the response characteristics by increasing the response from a single-button to a multiple-button response facilitated a 9% error of commission rate and response latency of 807 ms. Conversely, the traditional SART, which uses a single-button response, produces a relatively higher error-rate range (29%-55%) with a faster response latency range of 325-421 ms Helton, 2009;Helton, Head, & Russell, 2011;Helton, Kern, & Walker, 2009;Manly et al, 2003). As similarly found in point-and-click SARTs Wilson et al, 2018), changing the motor-response characteristics decreases response inhibition errors as measured by errors of commission; however, the cost of improved accuracy was slower response times to Go stimuli.…”
Section: Discussionmentioning
confidence: 91%
“…These aforementioned factors are likely to be compounded if the Soldier is not actually physically present on the battlefield but tele-present. Recently, it has been proposed that an additional contributing factor to friendly fire is response inhibition failures, which may be compounded as a function of the faster target-engagement tempo in modern combat (Wilson et al, 2018; Wilson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the many previous studies of the "speed-accuracy trade-off", inhibition of ongoing thought and action was focused when a mistake was noticed: if the stopping process wins, thought and action are inhibited (slow but more accurate); if the ongoing process wins, thought and action are executed (fast but less accurate) [15]. This inhibition mechanism has been thought to be related to the cortical-basal ganglia circuit; the basal ganglia output an inhibitory signal on the thalamus like a brake and control the speed and accuracy of some action initiated by cerebral cortical activity [16,22,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The task-positive motor activation most likely reflects a combination of motor action through button presses and its preparation and inhibition (when a 3 was presented). Previous research has shown that performance in motor-related vigilance tasks, such as the SART, depends on preparatory (motor) set [ 33 , 34 , 35 , 36 ]. In our study we observed significant task-positive activity in multiple motor regions that are considered to control the Bereitschaftspotential (readiness potential) as they continuously assess both the planning of potential motor responses and prevent false premature initiation by limiting activity in nonprimary motor cortical areas through the thalamus and basal ganglia [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%